Analisis Teoritis Pendekatan Resource-Based Learning dalam Meningkatkan Kemandirian Belajar : Sebuah Tinjauan Pustaka Sistematis - Sofyatun Nisa; Kini Tri Utami; Riza Faishol (CV. Lentera Literasi Indonesia, 2026)
This article aims to analyze the theoretical relationship between the Resource-Based Learning (RBL) approach and the enhancement of self-directed learning through a systematic literature review. The research background is based on the shift in the educational paradigm from teacher-centered to learner-centered, driven by technological developments and access to increasingly diverse learning resources. RBL is seen as a relevant approach to empowering learners in managing independent learning. However, previous studies tend to focus on specific learning outcomes without investigating the mechanisms underlying the relationship between RBL and self-directed learning in depth. Therefore, this study has the following objectives: (1) to identify key RBL principles that support self-directed learning; (2) to analyze the psychological and pedagogical mechanisms in the process; and (3) to map the supporting and inhibiting factors of RBL effectiveness in the context of developing self-directed learning. The research method used is a systematic literature review with a qualitative approach based on thematic analysis. Data were collected from SINTA-indexed national journals and international publications accessed through Google Scholar, the Garuda Portal, and the SINTA database, with publications limited to the last 10 years (2014–2024). The analysis procedure adapted the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework through the stages of identification, screening, eligibility assessment, and inclusion of articles. The validity of the findings was enhanced through source triangulation and peer debriefing. The results revealed three key principles of RBL: source diversity, learner autonomy, and inquiry-based learning. These three principles encourage independent learning through mechanisms of increasing self-efficacy, strengthening self-regulation, and shifting the locus of control to internal learners. The implementation of RBL is supported by factors such as teacher competence, the availability of learning resources, and a conducive school culture, but is hampered by the digital literacy gap, misaligned evaluation systems, and a dense curriculum load. This study provides an integrated conceptual framework for the development of empowering learning practices and recommendations for further empirical research.